MAINTAIN LIFESTYLE ENVIRONMENTS FOR SMOKERS (Tufts Archival Research Center, 2007)
Report discussing the objective to maintain lifestyle for smokers and generate allies for Philip Morris. Addresses three area of public smoking: workplace, hospitality and transport. Outlines work needed to further encourage new allies and discourage any legislation on regulation of cigarette smoking. Mentions alternative to legislation as ventilation or courtesy.